Arboretum untuk Green Campuss UIN Walisongo Semarang - Purnamaningrum, Arifah (Jounal of Enviromental Science Sustainable, 2021)
A sustainable green campus program requires a commitment to maintain the campus environment in order to remain of green campus values. One of them is commitment in providing green open space. Considering the land requirements for building construction are increasing, it is necessary to determine an area where construction is not permitted at that location. The location is devoted to green open space. Determination of a location as an arboretum can strengthen commitment to providing green open space in campus environment of UIN Walisongo Semarang. The multifunctional arboretum is very useful for the development of sustainable green campus. This study is to examine the arboretum as a supporter of green campus programs at UIN Walisongo Semarang. There are three potential locations to be used as arboretum of UIN Walisongo Semarang. Cluster concept that carries genetic conservation is suitable for the development of UIN Walisongo arboretum, beside considers the existing inventory. Needs of deep study about an inventory of existing flora and fauna, site conditions, and development plans for more appropriate arboretum for UIN Walisongo Semarang green campus.